2017
DOI: 10.1111/hdi.12543
|View full text |Cite
|
Sign up to set email alerts
|

Role of hepcidin‐ferroportin axis in the pathophysiology, diagnosis, and treatment of anemia of chronic inflammation

Abstract: Anemia of chronic inflammation (ACI) is a frequently diagnosed anemia and portends an independently increased morbidity and poor outcome associated with multiple underlying diseases. The pathophysiology of ACI is multifactorial, resulting from the effects of inflammatory cytokines which both directly and indirectly suppress erythropoiesis. Recent advances in molecular understanding of iron metabolism provide strong evidence that immune mediators, such as IL-6, lead to hepcidininduced hypoferremia, iron sequest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 92 publications
2
30
0
1
Order By: Relevance
“…Hepcidin response to an infection may be tissue, pathogen and inflammation specific (Schmidt, 2015). New hepcidin-ferroportin axis therapies have been proposed which have the potential to increase iron availability for erythropoiesis (Wang and Babitt, 2016;Langer and Ginzburg, 2017). However, the increase of hepcidin is not always present in the elderly with an inflammatory state, suggesting a more complex interaction (Ferrucci et al, 2010).…”
Section: Hepcidinmentioning
confidence: 99%
“…Hepcidin response to an infection may be tissue, pathogen and inflammation specific (Schmidt, 2015). New hepcidin-ferroportin axis therapies have been proposed which have the potential to increase iron availability for erythropoiesis (Wang and Babitt, 2016;Langer and Ginzburg, 2017). However, the increase of hepcidin is not always present in the elderly with an inflammatory state, suggesting a more complex interaction (Ferrucci et al, 2010).…”
Section: Hepcidinmentioning
confidence: 99%
“…7 On the other hand, increased IL-6 is also known to directly cause the down-regulation of ferroportin mRNA expression, thus resulting in decreased iron absorption. 8 Iron, being a constituent of various proteins and enzymes, is crucial to an array of biological processes ranging from tissue oxygenation, energy metabolism to bactericidal actions of the immune system. ID occurs when the absorption of iron is insufficient to meet the demands of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations showed that vitamin D concentrations [assessed by serum 25-hydroxyvitamin D (25(OH)D)] are inversely associated with hepcidin concentrations and positively associated with hemoglobin and iron concentrations. [12][13][14] Our study conducted in the population of pregnant women attending the Government Headquarter Hospital, Udhagamandalam highlights the potential correlation between vitamin D and iron deficiency anaemia. Net, only 101 subjects were presented for analysis.…”
Section: Resultsmentioning
confidence: 84%
“…There is overall paucity of clinical studies investigating whether adequacy of vitamin D affects blood Hemoglobin (Hb) levels. [12][13][14] The absorption and recycling of iron is under control of the hepcidinferroportin axis in humans. Iron is strictly regulated, because iron deficiency causes anemia and in excess promotes generation of reactive oxygen species, causing tissue injury and organ failure.…”
Section: Discussionmentioning
confidence: 99%